Hexachlorobenzene as a cause of porphyria turcica - Wray, Joe D.; Müftü, Yunus; Doğramacı, İhsan (The Turkish Journal of Pediatrics, 1962)
An outbreak of cutaneous porphyria in southeastern Turkey is traced to the ingestion of hexachlorobenzene treated wheat by the victims.The fact that seed wheat, treated with two commercial products containing hexachlorobenzene, was introduced into the region for the first time just prior to the outbreak of the disease is established. The reasons for the consumption of seed wheat by the local population are explored at length. Field studies, in which it was determined that everyone who developed the disease had eaten treated wheat, are reported, and it is further stated that no evidence was uncovered by the field investigators to indicate that any other etiologic factor could seriously be considered as the primary precipitating cause of this type of porphyria.In view of these facts, and the laboratory demonstration of the toxicity of hexachlorobenzene, it is concluded that the immediate precipitating agent in the Turkish type of porphyria (porphyria turcica) is hexachlorobenzene.